The internal determinants of gender diversity and its non-linear impact on firms' performance: Evidence from the listed companies in Palestine exchange - Abdelrahman J. K. Alfar; Nariman Abuatwan; Mohamed Elheddad; Mohammad Qaki (Journal of Risk and Financial Management, 2023)
This study mainly aims to test the impact of gender diversity on a firm's performance. Namely, the non-linear and the quantile impact on the listed companies in Palestine Exchange during the period 2010 to 2020. The study also aims to determine the impact of a firm's internal characteristics on gender diversity. The study uses instrument analysis, traditional panel models, and quantile regression to fulfil the aims. The results demonstrate the existence of a critical mass for the impact of gender diversity on firms' performance and that mass is about 30% for the ROA and 41% for the EPS.
Keywords: 650; firm performance; gender diversity; non-linear impact